The rate of spontaneous cleavage of the glycosidic bond of adenosine - Stockbridge, Randy B.; Schroeder, Gottfried K.; Wolfenden, Richard (Bioorganic chemistry, 2010)
We show that hydrolysis of the glycosidic C N bond of adenosine, previously known to be subject to hydrolysis in acid and base, also proceeds through a pH-independent mechanism with a rate constant of 4 × 10 −12 s −1 at 25 °C. Previous estimates of the rate of spontaneous cleavage of the glycosidic bond of adenosine were determined by extrapolating the rates of the acid- and base-catalyzed reactions to neutral pH. Here we show that cleavage also proceeds through a pH-independent mechanism. Rate constants were determined as a function of temperature at pH 7 and a linear Arrhenius plot was constructed. Uncatalyzed cleavage occurs with a rate constant of 3.7 × 10 −12 s −1 at 25 °C, and the rate enhancement generated by the corresponding glycoside hydrolase is ∼5 × 10 12-fold.